The use of Eculizumab and Tocilizumab in the treatment of Hyperhemolysis syndrome, a comprehensive literature review - Aqel, Ali; Al-Asa’d, Yousef; Al-kindi, Salam; Altouk, Jaafar; Zayed, Abdullah Al; Al-Abdulmalek, Abdulrahman; Yassin, Mohamed A. (Frontiers in Medicine, 2025)
Hyperhemolysis syndrome (HHS) is a rare but severe complication of red blood cell transfusion, characterized by the destruction of both the patient’s and donor’s red blood cells. This condition results in post-transfusion hemoglobin levels lower than pre-transfusion levels, often leading to profound anemia, tissue ischemia, and multiorgan failure. HHS predominantly affects individuals with hemoglobinopathies, particularly sickle cell disease. While the pathophysiology remains poorly understood, proposed mechanisms include bystander hemolysis via complement activation, suppression of erythropoiesis, macrophage-mediated RBC destruction. Refractory cases of HHS are managed with Eculizumab and Tocilizumab, targeting the complement pathway and macrophage activation, respectively. This review analyzed 22 reported cases of HHS identified through PubMed, Embase, and Google Scholar. Of these, 11 patients received Eculizumab, 10 received Tocilizumab, and 1 received both. The cohort had an mean age of 29.5 years, with 36.4% male and 63.6% female. Most patients had underlying hemoglobinopathies. Outcomes showed improvement in 18 patients without major side effects, while 1 patient showed no improvement, and 3 patients passed away. Despite promising results, concurrent use of other immune-modulating agents during treatment complicates attributing the observed efficacy to specific medications alone. Further studies are required to further evaluate the pathophysiology of HHS and assess the safety and effectiveness of these novel therapies.